The metabolic effect of combined liraglutide treatment and lifestyle modification on obese adolescents in a tertiary center, Riyadh - Babiker, Amir; Alfaraidi, Haifa; Aljarallah, Gadah; Albaraki, Joud; Alharbi, Reem; Alsomali, Nouf; Alkhalaf, Abeer; Yenugadhati, Nagarajkumar; Al Juraibah, Fahad; Al Alwan, Ibrahim (Frontiers in Endocrinology, 2025)
BackgroundObesity has increased in adolescents with a rising incidence of metabolic consequences, including type 2 diabetes, necessitating new pharmacotherapeutic approaches. Liraglutide is the first FDA-approved therapy for obesity in adolescents in less than a decade. We assessed its efficacy combined with lifestyle interventions in our patients.MethodsA retrospective cohort study was conducted at a specialized children hospital in Riyadh (2019–2022). All patients had simple, non-syndromic obesity and received intensive education on lifestyle modification. Data was collected from patients in two groups: Lifestyle modification (LifeSG) Vs Lifestyle and Liraglutide (LiraglG). Comparisons of two repeated measures obtained at T1 (baseline) and T2 (6-9 months) or T3 (9-12 months), including changes in body mass index (BMI), glycated hemoglobin (HbA1c) and other metabolic markers, were performed in the two matched groups using paired t-tests. Regression analysis using linear mixed models (SAS 9.4) were used to assess the effect of treatment status over time (P-value ≤ 0.05).ResultsData collected from 138 patients (n=69 in each group) with mean BMI and HbA1c of 35.78 kg/m2 and 5.85%, respectively. Notably, BMI declined by 0.48 kg/m2 over time in the LiraglG (p=0.003). An interaction effect (p=0.027) suggested a treatment impact until the first follow-up, which was not sustained thereafter. LifeSG exhibited no significant changes in biomarkers throughout T1-T3 period. In contrast, significant reductions were observed in BMI between T1-T2 (p=0.0057) and T1-T3 (p=0.010), total cholesterol (T1-T2) (p=0.023), alkaline phosphatase (T1-T3) (p<0.05) and low-density lipoprotein mean levels (T1-T3) (p=0.05) in the LiraglG group. A decline of 0.13% in A1c was observed in LiraglG; which may not clinically meaningful except in patients with pre-diabetes range of A1c (≥ 5.8%).ConclusionLiraglutide combined with lifestyle intervention is effective in treating obese Saudi adolescents, especially in the first 6-9 months. Continuous lifestyle intervention plays a key role in sustainability.